2015
DOI: 10.1016/j.bbamem.2015.07.018
|View full text |Cite
|
Sign up to set email alerts
|

Human lactoferricin derived di-peptides deploying loop structures induce apoptosis specifically in cancer cells through targeting membranous phosphatidylserine

Abstract: Host defense-derived peptides have emerged as a novel strategy for the development of alternative anticancer therapies. In this study we report on characteristic features of human lactoferricin (hLFcin) derivatives which facilitate specific killing of cancer cells of melanoma, glioblastoma and rhabdomyosarcoma compared with non-specific derivatives and the synthetic peptide RW-AH. Changes in amino acid sequence of hLFcin providing 9-11 amino acids stretched derivatives LF11-316, -318 and -322 only yielded low … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
79
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(98 citation statements)
references
References 66 publications
16
79
0
Order By: Relevance
“…Gly-Gly linker has previously been used in other CPP-AMP chimeras as described above (Hilchie et al 2013, Lemeshko 2013, while a Pro linker has been used by other research groups to create other dimer or retro-dimer peptides with improved cancer cell toxicity (Riedl et al 2015). In the presence of both hLF11-LFcinB1 chimeras, Jurkat cell killing was substantially increased compared to either component peptide alone (Fig.…”
Section: R a F Tmentioning
confidence: 93%
“…Gly-Gly linker has previously been used in other CPP-AMP chimeras as described above (Hilchie et al 2013, Lemeshko 2013, while a Pro linker has been used by other research groups to create other dimer or retro-dimer peptides with improved cancer cell toxicity (Riedl et al 2015). In the presence of both hLF11-LFcinB1 chimeras, Jurkat cell killing was substantially increased compared to either component peptide alone (Fig.…”
Section: R a F Tmentioning
confidence: 93%
“…Interestingly, N-terminal region of bLf, which shows a different consensus sequence (A 1 PRKN 5 ), is able to interact with cell membrane-associated GAGs similarly to hLf [125]. Moreover, Riedl and colleagues have shown that phosphatidylserine, a cytoplasmic membrane component largely represented on tumor cells, is a crucial target for the specific anti-cancer activity of human Lfcin (Lfcin-H) derivatives [126]. This primary selective interaction via cell surface receptors can explain the most archaic function ascribed to Lf, i.e., its cytotoxic activity.…”
Section: Lactoferrin and Cancermentioning
confidence: 99%
“…Specifically, peptides target negatively charged membrane components in the membrane, such as phosphatidylserine (PS), sialic acid or heparan sulfate. In fact, the exposure of the negatively charged lipid PS on the outer leaflet of the cancer cell membrane is a key difference between cancerous and non-cancerous cells, which are overall neutrally charged, owing to zwitterionic phosphatidylcholine and sphingomyelin (166,167).…”
Section: Mechanisms Of Action Of Bioactive Peptides Underlying Their mentioning
confidence: 99%